Prediction of Tool Lifetime and Surface Roughness for Nickel-Based Waspaloy - Shao-Hsien Chen; Chung-An Yu (Advances in Materials Science and Engineering)
In recent years, most of nickel-based materials have been used in aircraft engines. Nickel-based materials applied in the aerospace industry are used in a wide range of applications because of their strength and rigidity at high temperature. However, the high temperatures and high strength caused by the nickel-based materials during cutting also reduce the tool lifetime. This research aims to investigate the tool wear and the surface roughness of Waspaloy during cutting with various cutting speeds, feed per tooth, cutting depth, and other cutting parameters. Then, it derives the formula for the tool lifetime based on the experimental results and explores the impacts of these cutting parameters on the cutting of Waspaloy. Since the impacts of cutting speed on the cutting of Waspaloy are most significant in accordance with the experimental results, the high-speed cutting is not recommended. In addition, the actual surface roughness of Waspaloy is worse than the theoretical surface roughness in case of more tool wear. Finally, a set of mathematical models can be established based on these results, in order to predict the surface roughness of Waspaloy cut with a worn tool. The errors between the predictive values and the actual values are 5.122%∼8.646%. If the surface roughness is within the tolerance, the model can be used to predict the residual tool lifetime before the tool is damaged completely. The errors between the predictive values and the actual values are 8.014%∼20.479%.